2020
DOI: 10.1155/2020/2935278
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Lipid Profiles in Plasma Allows Cardiometabolic Risk Factor Clustering in Children with Metabolically Unhealthy Obesity

Abstract: Hypertension, central obesity, hyperglycemia, and dyslipidemia are key risk factors for cardiovascular disease. However, the specific factors contributing to the development of unfavorable cardiometabolic characteristics in children with obesity are unknown. In this study, we investigated the cross-sectional relationships between cytokines, irisin, and fatty acid (FA) composition in plasma in school-age children with metabolically healthy and unhealthy obesity (MHO and MUO, respectively) of the same age and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…We showed that lipids are the most crucial group of altered metabolites in obese children compared to the non-obese control group. This observation aligns with the other metabolomics studies on obesity in adults [ 38 , 39 ] and limited data on pediatric populations [ 40 , 41 ]. Obesity is associated with elevated levels of TGs [ 42 , 43 ], sphingolipids [ 44 ], SM [ 45 ], CE [ 43 ], and phospholipids (PLs) [ 46 ] in adult obese patients.…”
Section: Discussionsupporting
confidence: 90%
“…We showed that lipids are the most crucial group of altered metabolites in obese children compared to the non-obese control group. This observation aligns with the other metabolomics studies on obesity in adults [ 38 , 39 ] and limited data on pediatric populations [ 40 , 41 ]. Obesity is associated with elevated levels of TGs [ 42 , 43 ], sphingolipids [ 44 ], SM [ 45 ], CE [ 43 ], and phospholipids (PLs) [ 46 ] in adult obese patients.…”
Section: Discussionsupporting
confidence: 90%
“…Separation of FAMEs was performed in a fused-silica SP-2380 capillary column (100 m × 0.25 mm i.d., 0.2 µm film thickness; Supelco, Bellefonte, PA, USA). Chromatographic parameters, and FAMEs identification and quantification were performed according to Castillo et al [ 19 ]. Quantification for each compound, and the total amount of fatty acids were calculated by the AOAC method 996.06 [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Avocado subsamples (from study I or II ), AcO-avocadene, which is an NMR-characterized free acetogenin analytical standard ( Rodríguez-Sánchez et al, 2013 ), and Avosafe ® were independently derivatized ( Castillo et al, 2020 ). Undecanoic acid (200 ppm, Nu Chek Prep Inc., MA, United States) was used as an internal quantification standard.…”
Section: Methodsmentioning
confidence: 99%
“…A standard mixture containing 39 FAMEs (GLC 566, Nu Chek Prep Inc., MA, United States) or standardized AcOMEs obtained in the previous section ( Study II ) were analyzed by GC–MS chromatography (Agilent 7890B/5977A, Agilent Technologies Inc., CA, United States) to identify the lipids. A previously developed method was used ( Castillo et al, 2020 ). Having as reference fragmentation patterns of FAMEs ( Jabbar et al, 2014 ; Busta et al, 2016 ) and Mclafferty rearrangement characteristic of esters ( McLafferty, 1956 ; Weiler, 1972 ), the expected fragmentation patterns of each of the free AcO-acetogenins reported here (based on their structure) were matched to their observed mass spectra ( Supplementary Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation